Topical protection of mice laryngeal mucosa using the natural product cashew gum. (27th October 2017) - Figueiredo, Aline A.; Santana, Ana P. M.; Nicolau, Lucas A. D.; Batista‐Lima, Francisco J.; Wong, Deysi V. T.; Lucetti, Larisse T.; Batista, Gabriela L. P.; Caminha, Natália A.; Medeiros, Jand V. R.; Silva, Durcilene A.; Leite, José R. S. A.; Santos, Armênio A.; et al.
Abstract : Objectives/Hypothesis: Evaluate the effect of in vitro exposure of mice laryngeal mucosa to solutions that simulated human gastric juice and to assess the topical protective effect of cashew gum on mice laryngeal mucosal integrity in vitro. Study Design: Animal study. Methods: Murine (Swiss) laryngeal samples were mounted in Ussing chambers. The luminal side of biopsies was exposed to solutions of different acidity with or without pepsin and/or taurodeoxycholic acid (TDC). Transepithelial electrical resistance (TER) was continuously recorded. The topical protective effect of cashew gum solution was evaluated by precoating the biopsies before the exposure with a solution at pH 5 containing 5 mM TDC. Changes in TER and mucosal permeability to fluorescein were measured. Results: Exposure of laryngeal mucosa to acidic solutions containing pepsin and TDC provoked a pH‐dependent drop in TER with the maximal effect at pH 1, but still present at pH 5 (weakly acidic). The exposure of the laryngeal mucosa to a solution of pH 5 with TDC, but not with pepsin, produced a dose‐dependent decrease in TER. Precoating the mucosa with cashew gum prevented the reduction of TER and increased transepithelial permeability by exposure to a solution at pH5 containing TDC. Conclusions: Weakly acidic solutions containing bile acids can produce impairment of laryngeal epithelial barrier, which may be protected by topical treatment with cashew gum. Level of Evidence: NA. Laryngoscope, 128:1157–1162, 2018